Catalogue of fungi in China 2. Ramaria from northern China - Ying Li; Ning Mao; Yu-Xing Zhang; Hao-Yu Fu; Li Fan (Mycology)
The species of Ramaria are coralloid-fungi with intricately branched and vividly coloured basidiomata. There are many studies on the genus Ramaria in China, but molecular phylogenetic analysis is rarely employed. In this study, we performed a multigene phylogenetic analysis to identify Ramaria species in Shanxi Province of northern China. Phylogenetic analyses based on four loci, the internal transcribed spacer region of nuclear ribosomal DNA (ITS), the nuclear large subunit ribosomal DNA (nrLSU), ATPase subunit 6 (atp6), and mitochondrial small subunit ribosomal DNA (mtSSU), revealed 13 Ramaria species from our collections. Combined with morphological examinations, 12 of them were identified as new species, plus a new report to China. The thirteen species were described and illustrated in this paper.